Mozambique is suffering a military expression of a political problem. An interview with historian Michel Cahen for the Rosa Luxemburg Foundation Southern Africa - (:unkn) unknown (My University, 2016)
Mozambique is currently facing one of the most challenging tests of its capacity to resolve the country’s political, economic and social challenges. Politically, a ceasefire agreement signed between the Government of Frente de Libertação de Moçambique (FRELIMO) and the main opposition party, the Resistência Nacional de Moçambique (RENAMO) on 24 August 2014 was short-lived. It only served to clear the way for the country’s general elections on 15 October 2014, at which time the highly contested results by RENAMO brought about another round of military conflict. Economically, the national currency, Metical, has been consistently devaluing against, for example, the South African Rand, the American Dollar and the Euro, when potential gains from newly discovered resources (e.g. offshore gas) have failed to produce any tangible improvement to people’s lives. This, in conjunction with the discovery of hidden debt of 1, 4 billion USD, led partners like the International Monetary Fund (IMF), the World Bank (WB) and the British to suspend further financial aid to the country. It is therefore expected that these political and economic developments will lead to political upheaval if the Government does not address questions fast and adequately. To better understand Mozambique’s current political developments from a political-historical perspective, Fredson Guilengue, Programme Manager at the Rosa Luxemburg Stiftung Southern Africa (RLS) interviewed historian Michel Cahen (MC). Michel Cahen is an authority on Portuguese colonisation in Africa and a political analyst of Portuguese speaking African Countries (PALOPs). He is the Director of Research at the Centre National de la Recherche Scientifique (CNRS) at “Les Afriques dans le monde” Research Centre at the Institute for Political Studies in Bordeaux, France. As an accredited historian of Mozambican and Angolan contemporary history, Cahen has written extensively on Mozambique’s political develop
Keywords: African Research